2016
DOI: 10.1111/sode.12214
|View full text |Cite
|
Sign up to set email alerts
|

Differential parenting and children's social understanding

Abstract: In the current study, a curvilinear association was examined between differential parenting and children's social understanding as measured using standardized assessments and behavioral observations. Social understanding was comprised of theory-of-mind and behavior indicating understanding of others' minds (i.e., cognitive sensitivity and internal state talk and reasoning during sibling interactions). Data came from a community sample of 372 children (51.6% males; M age 5 5.57, SD 5 0.77), their younger siblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The nature of the parent–child relationship is important to consider (Pauker, Perlman, Prime, & Jenkins, 2017), and research has shown that this relationship worsens for the sibling who is disfavored (Boll et al, 2003). Likewise, the relationship between siblings is negatively affected when one is treated differently.…”
Section: Siblings and Parental Favoritismmentioning
confidence: 99%
“…The nature of the parent–child relationship is important to consider (Pauker, Perlman, Prime, & Jenkins, 2017), and research has shown that this relationship worsens for the sibling who is disfavored (Boll et al, 2003). Likewise, the relationship between siblings is negatively affected when one is treated differently.…”
Section: Siblings and Parental Favoritismmentioning
confidence: 99%
“…This relationship emphasizes moderate parental control (Pauker, Perlman, Prime, & Jenkins, 2017). Moreover, empirical studies have shown that children tend to develop best under moderate parental control, behave in a more deviant manner under low parental control (because of inadequate parental attention and supervision), and develop rebellious attitudes and experience developmental problems under high parental control (because it restricts their autonomy and independent thinking).…”
Section: Overparenting and Creativitymentioning
confidence: 98%
“…The nonlinear relationship between parenting and children's development has received growing attention; related topics include the U‐shaped relationship and threshold effect (Kokkinos, Antoniadou, Asdre, & Voulgaridou, ; Segrin, Woszidlo, Givertz, Bauer, & Taylor Murphy, ). This relationship emphasizes moderate parental control (Pauker, Perlman, Prime, & Jenkins, ). Moreover, empirical studies have shown that children tend to develop best under moderate parental control, behave in a more deviant manner under low parental control (because of inadequate parental attention and supervision), and develop rebellious attitudes and experience developmental problems under high parental control (because it restricts their autonomy and independent thinking).…”
Section: Related Theories and Proposed Hypothesesmentioning
confidence: 99%
“…Permissive parents tend to be very loving, yet provide less guidelines and rules. In this type of parenting the parents do not expect mature behavior from their children and often seem more like a friend than a parental figure (Ogunleye et al,2013;Pauker et al, 2017). Emotional intelligence refers to the capability of a person to manage and control his emotions for performing the specific task.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional intelligence refers to the capability of a person to manage and control his emotions for performing the specific task. In educational context emotional intelligence is a skill that identify the positive emotions and understandings that contribute the academic success of the students (Cotton & Wikelund, 2001;Pauker et al, 2017). The Goleman (2001) and Gardner (1993) theories of emotional intelligence have elicited great interest both in the academic and the non-academic world.…”
Section: Introductionmentioning
confidence: 99%